2018
DOI: 10.1111/tmi.13116
|View full text |Cite
|
Sign up to set email alerts
|

High seroprevalence of dengue virus indicates that dengue virus infections are frequent in central and eastern Sudan

Abstract: The majority of the population in central and eastern Sudan has been infected with dengue viruses, many people repeatedly. The high seroprevalence underscores the need for extended dengue surveillance in Sudan, broad disease awareness in medical institutions and in the population and diagnostic capacity building for severe dengue infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…This includes analyzing the studies sub-grouped by study type, location, and the test performed to detect DENV infection. Temporal variation was investigated by sub-grouping studies by the diagnostic test performed, IgG to assess the previous exposure to the virus, and IgM to assess the recent acute infection [ 33 ]. The prevalence of the DENV-IgG 38% (95% C.I.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This includes analyzing the studies sub-grouped by study type, location, and the test performed to detect DENV infection. Temporal variation was investigated by sub-grouping studies by the diagnostic test performed, IgG to assess the previous exposure to the virus, and IgM to assess the recent acute infection [ 33 ]. The prevalence of the DENV-IgG 38% (95% C.I.…”
Section: Discussionmentioning
confidence: 99%
“…26–51%) was significantly higher than DENV-IgM 22% (95% C.I. 13–31%) indicating that the DENV transmission was likely both endemic as well as epidemic [ 33 ]. The estimated seroprevalence of DENV was similar between community-based and hospital-based studies with 26% (95% C.I.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, studies reported a high prevalence (67%) of DENV infections in Sudan and up to 89% in the coastal area. They highlighted that most people in these areas were infected repeatedly, and reported that all DENV (1-4) serotypes are circulating in the area [52,53]. Recently, DENV-1 and 3 emerged and caused an outbreak of dengue fever in the Darfur area, western Sudan [54].…”
Section: Dengue Virusmentioning
confidence: 99%
“…The severity of DENV infection varies from mild fever to complicated clinical hemorrhagic disease leading to shock and subsequent death [6][7][8]. In the recent years, DENV has spread significantly to different States of Sudan [9][10][11][12]. Currently, DENV infection constitutes one of the major unresolved public health problems in the country.…”
Section: Backgroudmentioning
confidence: 99%